Build-up and performance test of a novel solar thermal roof for heat pump operation - Buker, Mahmut Sami; Riffat, Saffa (Taylor & Francis, 2017)
Global increase in energy demand and fossil fuel prices loaded ever-increasing pressure on identifying and implementing new means to utilise clean and efficient energy resources. Due to the environmental benefits, technical and economic possibilities of Solar-Assisted Heat Pump Systems, there has been a growing interest for such hybrid systems with a variety of system configurations for various climates. International Energy Agency Task 44 of the Solar Heating and Cooling Programme has recently started working on finding methods to most effectively use solar heat pump systems for residential use. In the present study, a novel solar thermal roof collector was developed by primarily exploiting components and techniques widely available on the market and coupled with a commercial heat pump unit. The proposed indirect series Solar-assisted Heat Pump system was experimentally tested and system performance was investigated. Yet, the analysis based on indoor and outdoor testing predominantly focuses on the solar thermal roof collector. A detailed thermal model was developed to describe the system operation. Also, a computer model was set up by using Engineering Equation Solver to carry out the numerical computations of the governing equations. Analyses show that the difference in water temperature could reach up to 18°C while maximum thermal efficiency found to be 26%. Data processing of the series covering the test period represents that Coefficient Performance of the heat pump (COPHP) and overall system (COPSYS) averages were attained as COPHP = 3.01 and COPSYS = 2.29, respectively. An economic analysis points a minimum payback period of about three years for the system.